Creating Environmentally Sustainable Mosques: Combining Religious Principles With Ecological Practices - Ahmad Fajri Asshidiqi; Alfiani Rif'atus Sholihah (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: Global challenges like climate change and environmental degradation have led various sectors, including religion, to engage in mitigation and adaptation efforts. In Indonesia, home to the largest Muslim population, mosques possess substantial potential to drive environmental sustainability. This study examines how Islamic principles can be integrated with ecological practices to create sustainable mosques in Indonesia. By analyzing concepts such as khilafah (human leadership on earth), amanah (trust from God to protect nature), and mizan (balance). The study uses theoretical analysis and literature review, focusing on integrating Islamic theological principles. It reviews classical and contemporary Islamic literature on environmental management, linking Islamic teachings on nature protection with modern ecological practices. Findings show that the concept of khalifah designates humans as stewards of the earth, responsible for managing natural resources wisely. Mosques can become platforms for environmental education, encouraging worshippers to embrace their role as khalifah through programs highlighting Islamic teachings on nature. The study addresses the challenges of implementing eco-friendly mosque concepts in Indonesia and offers solutions based on religious values. This research aims to enhance understanding of mosques' roles in global sustainability, particularly in Indonesia, and showcase their potential contributions to climate change mitigation and environmental preservation for future generations.